PENENTUAN KADAR GLUKOSA DAN FRUKTOSA PADA MADU RANDU DAN MADU KELENGKENG DENGAN METODE KROMATOGRAFI CAIR KINERJA TINGGI - Ratnayani, K.; Dwi Adhi S., N. M. A.; Gitadewi, I G. A. M. A. S. (Jurnal Kimia (Journal of Chemistry); Vol. 2, No. 2 Juli 2008)
Honey is composed of reducing sugars i.e. glucose, fructose, and maltose. The concentration of sugar honey is determined as total reducing sugars, so the concentration of each sugar which compose the honey is not known. The research aims to determine the concentrations of glucose and fructose of honey from different cotton tree honey and longan honey HPLC using. The HPLC operational condition was as follows 80oC of column temperature and 1 mL/minutes of flow rate, using metacarb 87C column and deionized watr as eluent. The detection was carried out by using refractive index detector, where glucose and fructose can be separated at retention times of 6 and 7 minutes. The result of research showed that the concentration of glucose in cotton tree honey was 27.13 % and in longan honey was 28.09 %. the concentration of fructose in cotton tree honey was 40.99 % and in longan honey was 40.03 %. Thees results showed that the quality standard on the total concentration of reducing sugar (60 %) was met by both types of honey. The total concentration of reducing sugar of cotton tree honey was 68.12 % and of longan honey was 68.12 %.
Keywords: glucose, fructose, maltose, HPLC, honey